Adsorption Mechanisms of Phenol and Methylphenols on Organoclays - Özlem Ceyhan; Hülya Güler; Raif Güler (Adsorption Science & Technology)
Eight clay–organic complexes were synthesized by placing quaternary ammonium cations (QUATs) on to bentonite (B) and kaolinite (K) by cation exchange. The organic cations used were hexadecyltrimethylammonium (HDTMA), dodecyltrimethylammonium (DDTMA), trimethylphenylammonium (TMPA) and tetramethylammonium (TMA). These organoclays were characterized via their organic carbon contents with the aid of XRD and FT-IR spectroscopic analyses. The organoclays were examined for their ability to adsorb phenol (P) and several of its methyl congeners [2,4-dimethylphenol (2,4-DMP) and 2,4,6-trimethylphenol (2,4,6-TMP)]. It was shown that inorganoclays (Na–clays) and organokaolinites were incapable of adsorbing any of these organic pollutants. It was also determined that the adsorption of phenol compounds from water decreased in the order: 2,4,6-TMP > 2,4-DMP > P for HDTMA–B and DDTMA–B, 2,4-DMP > P > 2,4,6-TMP for TMPA–B and P > 2,4-DMP > 2,4,6-TMP for TMA–B. With n-hexane as a solvent a different adsorption trend was found, which depended on the type and degree of solvent interaction with the organic compounds and the organoclays. It was observed that the degree of adsorption of phenols on to organoclays was dependent on the relative adsorbent-adsorbate energies and adsorbate–solvent interactions. The adsorption isotherms of phenols on to organophilic clays were evaluated according to the Giles classification.